2021
DOI: 10.1016/j.ymthe.2021.08.001
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of the efficacy and safety of COVID-19 vaccines

Abstract: The numbers of cases and deaths from coronavirus disease 2019 (COVID-19) are continuously increasing. Many people are concerned about the efficacy and safety of the COVID-19 vaccines. We performed a comprehensive analysis of the published trials of COVID-19 vaccines and the real-world data from the Vaccine Adverse Event Reporting System. Globally, our research found that the efficacy of all vaccines exceeded 70%, and RNA-based vaccines had the highest efficacy of 94.29%; moreover, Black or African American peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
2
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(111 citation statements)
references
References 26 publications
5
94
2
5
Order By: Relevance
“…Neither myocarditis nor pericarditis was observed, a finding consistent with the low frequency of these adverse events with real-world use of BNT162b2 in other age groups. 32 …”
Section: Discussionmentioning
confidence: 99%
“…Neither myocarditis nor pericarditis was observed, a finding consistent with the low frequency of these adverse events with real-world use of BNT162b2 in other age groups. 32 …”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the ORF1ab, ORF8, and nucleocapsid protein also occur [219]. Cai et al [220] reported a comprehensive analysis demonstrating that, in terms of efficacy, RNA-based vaccines are the most effective and are capable of reaching greater than 94% efficacy. The authors attribute this achievement to the strong immunogenicity and effective presentation of SARS-CoV-2 antigens to the immune system of these vaccines.…”
Section: Efficacy Of Rna-based Vaccines Against Sars-cov-2 Variantsmentioning
confidence: 99%
“…We recently published a paper in Molecular Therapy that studies the efficacy and safety of COVID-19 vaccines in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). 1 Here, we report analyses of the efficacy of COVID-19 vaccines against the delta variant. We evaluated the efficacy of COVID-19 vaccines from the perspective of overall infection, severe infection, and fatal infection, following receipt of 3 types of vaccines: messenger RNA (mRNA)-based vaccine; viral vector (non-replicating) vaccine; and inactivated vaccine (no data have been reported for other types of vaccines).…”
Section: Main Textmentioning
confidence: 99%